The vertical jump height of soccer players after static overstretching - Vieira do Amaral Vasconcellos, F.; Gil da Costa Mendes De Salles, P.; Achour Junior, A.; Braga de Mello, D.; Martin Dantas, E. H. (Human Movement, 2012)
The purpose of this study was to assess the effect of static overstretching on performing a vertical jump. Methods. A methodological model was used, using descriptive and comparative methods on 45 randomly selected under-15-year-old male soccer players. Three jump test measurements were taken over a period of several days, where the first measurement included a pre-test in order to familiarize the athletes with using a contact mat, where maximum vertical jump height was recorded as a control. The second measurement had the athletes perform a vertical jump after static overstretching of the lower limbs. The third test had the athletes perform another vertical jump with no overstretching as another control. Results. The results found a significant difference in vertical jump heights (?% = 34.1%, p Conclusions. The usage of such a static overstretching method negatively influences the vertical jump within the tested group of under-15 male soccer players.